Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Get quick and reliable solutions to your questions from a community of experienced professionals on our platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

What is the solution to the system below?
y = -3x - 2
6x + 2y = -4


Sagot :

Answer:

Infinitely many solutions

Step-by-step explanation:

Since y=-3x-2, plug it in (2)

6x+2(-3x-2)=-4.

Distribute:

6x-6x-4=-4

-4=-4

Infinetly many solutions.

Hope this helps :)